Minireview on the Electrocatalytic Ammonia Oxidation Reaction for Hydrogen Production and Sewage Treatment - Liu, Hanwen; Xu, Xiaomin; Guan, Daqin; Shao, Zongping (2024)
Ammonia electrolysis represents an advanced and promising approach for both hydrogen production and sewage treatment. Nevertheless, they confront a significant obstacle in the form of the electrocatalytic ammonia oxidation reaction (AOR), mainly attributable to the sluggish reaction kinetics. This minireview comprehensively discusses the intricate mechanisms and critical parameters that govern the AOR for hydrogen production and sewage treatment. Various influential factors, including pH levels, voltage, and temperature, are systematically discussed, shedding light on their vital roles in modulating the AOR. Additionally, catalysts, such as pure metals, alloys, metal hydroxides, and metal oxides, are comprehensively reviewed, with the goal of elevating the efficiency of ammonia electrooxidation. On the basis of current research, prospects of electrolyte optimizations and catalyst improvements are systematically discussed.